COMPARISON OF EMG OF BICEPS FEMORIS AND GASTROCNEMIUS IN LEG CURL IN DORSIFLEXION AND PLANTAR FLEXION (Fiep Bulletin - online, 2014)
The activities in fitness centers won many fans in the last years, among the various choices of activities, we are against resistance training as one of the most sought through classes in bodybuilding and gymnastics located among others. These activities located the exercises are important tool for the preparation of the training programs. In this context arises from the surface electromyography as instrumentation that helps in the acquisition of knowledge of the exercises located, where possible to determine electrical activity of muscles investigated, having been chosen in this study to check the electrical activity of muscles gastrocnemius and biceps femoris in the performance leg curl, when held in plantar flexion and dorsiflexion. Part of the study 06 individuals the male gender, not practitioners of bodybuilding, chosen for convenience, without damage to the locomotor apparatus and or disease, with average age of 23.7 ± 4.6 years, not obese. The data received treatment descriptive and inferencial using the STATISTICA program. Through the Kolmogorov-Smirnov test verified that the data showed normal distribution, and thus to compare the two positions, was used one-way ANOVA with a post-hoc test of Tukey, with significance level of 0.05. The comparison (ANOVA) between the two positions was held in the values of RMS of each muscle. The results pointed out that the medial and lateral gastrocnemius showed higher activity EMG on condition of plantar flexion (34.11 ± 7.12; 36.88 ± 6.59, respectively) and the biceps femoris presented greater activity on condition dorsiflexion (41,23 ± 7,42).The values were obtained when compared the activities of the muscles involved in the study.
Keywords: EMG; dorsiflexion; plantar flexion